Glucocorticoid receptor regulates organic cation transporter 1 (OCT1, SLC22A1) expression via HNF4α upregulation in primary human hepatocytes - Rulcova, Alice; Krausova, Lucie; Smutny, Tomas; Vrzal, Radim; Dvorak, Zdenek; Jover, Ramiro; Pavek, Petr (Pharmacological reports, 2013)
BACKGROUND: Organic cation transporter 1 (OCT1, SLC22A1) is a membrane transporter that is important for therapeutic effect of the antidiabetic drug metformin. Its liver-specific expression in hepatocytes is strongly controlled by hepatocyte nuclear factor-4α (HNF4α). HNF4α expression and transcriptional activity have been demonstrated to be augmented by glucocorticoid receptor (GR) in human hepatocytes and rodent livers. METHODS: It was examined whether GR activation indirectly induces OCT1 gene expression via HNF4α up-regulation in primary human hepatocytes. We also examined which other transcription factors are involved in OCT1 gene expression and whether they are regulated by dexamethasone using qRT-PCR and gene reporter assays. RESULTS: We found that dexamethasone significantly up-regulates OCT1 mRNA and protein in normal primary human hepatocytes, but not in hepatocyte-derived tumor cell lines HepG2 and MZ-Hep1. Consistently, we observed that HNF4α is induced by dexamethasone in primary human hepatocytes, but not in hepatocyte tumor-derived cell lines. Viral transduction of MZ-Hep1 cells with the expression constructs for HNF4α, CCAAT/enhancer binding proteins β (C/EBPβ) and peroxisome proliferator-activated receptor-γ coactivator 1α (PGC1α) demonstrated significant roles of the transcription factors in OCT1 gene regulation. We found that expression of OCT1 mRNA in human livers significantly correlates with C/EBPβ and HNF4α mRNAs expression and that C/EBPβ co-transfection stimulates OCT1 gene reporter construct in HepG2 cells. Nevertheless, neither C/EBPβ nor PGC1α were upregulated in human hepatocytes by dexamethasone. CONCLUSION: We can conclude that GR-induced expression of HNF4α may contribute to indirect OCT1 gene up-regulation by dexamethasone in primary human hepatocytes, but not in hepatocyte-derived tumor cell lines.
Keywords: přenašeč organických kationtů 1; messenger RNA; Hepatocytes; transdukce genetická; buňky Hep G2; Up-Regulation; Hepatocyte Nuclear Factor 4; Primary Cell Culture; transfekce; upregulace; Time Factors; Glucocorticoids; PPARGC1A; glukokortikoidy; primární buněčná kultura; Hep G2 Cells; Transcription Factors; hepatocytární jaderný faktor 4; Receptors, Glucocorticoid; transkripční faktory; hepatocyty; CCAAT-Enhancer-Binding Protein-beta; Peroxisome Proliferator-Activated Receptor Gamma Coactivator 1-alpha; RNA, Messenger; Humans; dexamethason; časové faktory; Transfection; Transduction, Genetic; Dexamethasone; Organic Cation Transporter 1; protein beta vázající zesilovač transkripce CCAAT; receptory glukokortikoidů; lidé